Preparation and characterization of a de-cellularized rabbit aorta as a promising scaffold in vascular tissue engineering - Song, L; Duan, P; Zhou, Q (Cellular and Molecular Biology, 2016)
Development of scaffold is essential for promoting and supporting healing process. This study aims to establish a decellularized rabbit aorta for clinical vascular tissue engineering therapy. We successfully prepared decellularized small-diameter aortic scaffolds and investigated several properties of this engineered vascular tissue scaffolds, including cell adhesion, hydrophilicity, cytotoxicity, biocompatibility. Results showed that decellularized aortas have a porous structure with few cell remnants as examined by histochemistry and scanning electron microscopy. Both vascular smooth muscle cells (VSMCs) and endothelial cells (ECs) cultured on decellularized aortas were adhered and proliferated well. Cell adhesion rates of rat VSMCs and ECs reached to 64.32±2.03% and 52.77±1.19%, respectively. VSMCs were able to migrate into outer surface of scaffolds. Hydrophilisity reached its maximal rate at 519±23% in 12 h. Importantly, no overt cytotoxicity was observed when grown in extraction solution of aortic scaffolds. Lastly, we also engrafted cell-scaffolds subcutaneously into nude mice in vivo. Implanted scaffold structure and proliferation of seeded cells were well maintained up to 8 weeks. In conclusion, we successfully prepared a decellularized rabbit aorta that not only largely maintains its extra-cellular structure, but also shows little toxicity. It may constitute a potential tool as a small diameter scaffold in vascular tissue engineering.